Didactics and communication. habermas’ contributions to education - Gómez Duarte, Leonardo; Peñaloza Jiménez, Gonzalo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article aims at establishing the possible bridges, agreements, or disagreements between the Theory of Communicative Action (TCA) and didactics. It emphasizes on the necessary relationship between didactics and debates on the function, goals, and nature of education itself. For this purpose it is firstly presented the relationship between communication and education, then the TCA’s basic elements related to didactics, finally, as a conclusion, some agreements and disagreements between the TCA and didactics are formulated. The frame of this work is the discussion about the role that a critical theory can play when analyzing the sense of education and its practice.